2009
DOI: 10.1007/s00056-009-0814-1
|View full text |Cite
|
Sign up to set email alerts
|

Guided Tissue Regeneration and Orthodontics. A Review of the Literature

Abstract: Guided tissue regeneration is a common form of treatment in dentistry nowadays. The orthodontist will inevitably have to deal with patients needing such therapy more often in the future. This review of the literature addresses the question of whether and if so, how patients with these medical requirements can be treated. We have systematically reviewed the current literature for recommendations, guidelines and problems associated with this treatment. Our data evaluation led us to conclude that such treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
7
0
5
Order By: Relevance
“…The clinical outcomes of this combined approach are promising, with increased connective tissue attachment levels reported in selected cases . A recent review of the literature, however, identified significant methodological heterogeneity and a lack of high‐quality studies in this area . Encouragingly, the use of bone substitutes to treat localized periodontal defects and augment atrophied alveolar ridges does not seem to have an adverse effect on orthodontic tooth movement in animals .…”
Section: Orthodontic Space Closurementioning
confidence: 99%
“…The clinical outcomes of this combined approach are promising, with increased connective tissue attachment levels reported in selected cases . A recent review of the literature, however, identified significant methodological heterogeneity and a lack of high‐quality studies in this area . Encouragingly, the use of bone substitutes to treat localized periodontal defects and augment atrophied alveolar ridges does not seem to have an adverse effect on orthodontic tooth movement in animals .…”
Section: Orthodontic Space Closurementioning
confidence: 99%
“…Moreover, the literature revealed that light continuous forces (5 to 15 g) were recommended in a compromised periodontum, and the range of the commencement of tooth movement after periodontal surgery ranged from 7 days to 1 year 20‐29 . Lack of information about the effective and safe timing in which to start the movement probably justified this huge range; in fact, severe root and bone resorption could be the major negative effects of moving teeth in immature bone.…”
Section: Introductionmentioning
confidence: 99%
“…Melsen et al, on the other hand, show that decreased periodontal orthodontic movement may promote periodontal regeneration and bone apposition in intrusion movements with low and constant periodontal pressures 11,12 These clinical findings are confirmed by animal experiments 2,15 . Tissue regeneration techniques induced with EMD allow attachment gains of 1.08 mm compared to the control group at 1 year and of 1.2 mm when EMD is added to autogenous bone 18 , which represents a significant gain at the root level.…”
Section: Repair or Regeneration Of The Periodontal Attachment Orthodomentioning
confidence: 92%